An Educational Study on the Impact of Ground Control Point (GCP) Quantity and Distribution on Orthophoto Geometric Accuracy in UAV Mapping - Randy M. Oswara; Devit Rahmawati (Civiliza Publishing, Indonesia., 2026)
The accuracy of orthophoto geometry from Unmanned Aerial Vehicle (UAV) mapping results is highly dependent on the quality of Ground Control Points (GCPs) as georeference references. This study aims to analyze the effect of the number and distribution pattern of GCPs on the accuracy of orthophoto geometry in the operational area of ​​PT Sumber Cahaya Mineral, Jambi. The method used is an experiment by comparing three configuration scenarios: no GCPs, three GCPs, and four GCPs. Accuracy measurements use the Root Mean Square Error (RMSE), Circular Error 90% (CE90), and Linear Error 90% (LE90) indicators referred to in BIG Regulation No. 6 of 2018. The results of the analysis show that the use of three GCPs with optimal geometric distribution patterns produces the highest accuracy (RMSE 0.00965 m), compared to four GCPs (RMSE 0.01636 m). This finding confirms that increasing the number of GCPs does not always increase accuracy, but rather spatial distribution (distribution pattern) is the main key, as supported by the basic theory of land surveying and photogrammetry.